2020
DOI: 10.1371/journal.pone.0241825
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a 30-day mortality index based on pre-existing medical administrative data from 13,323 COVID-19 patients: The Veterans Health Administration COVID-19 (VACO) Index

Abstract: Background Available COVID-19 mortality indices are limited to acute inpatient data. Using nationwide medical administrative data available prior to SARS-CoV-2 infection from the US Veterans Health Administration (VA), we developed the VA COVID-19 (VACO) 30-day mortality index and validated the index in two independent, prospective samples. Methods and findings We reviewed SARS-CoV-2 testing results within the VA between February 8 and August 18, 2020. The sample was split into a development cohort (test pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
118
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 87 publications
(127 citation statements)
references
References 24 publications
8
118
1
Order By: Relevance
“…However, previous research has established that after adjusting for age, sex, race, ethnicity, region, and residence type, all of which were accounted for in this study, total disease burden between veterans and non-veterans does not differ 69. In separate analyses, we developed a predictive index based on Veterans Affairs data70 and have since shown that the risk of covid-19 mortality associated with age, sex, and comorbid disease diagnoses that we observed in Veterans Affairs data was consistent across other academic and national healthcare samples in the US 71. Our key finding in the current analysis has also been shown in smaller, non-veteran healthcare systems1314; thus, effects reported in this study are probably generalizable to the wider US population.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous research has established that after adjusting for age, sex, race, ethnicity, region, and residence type, all of which were accounted for in this study, total disease burden between veterans and non-veterans does not differ 69. In separate analyses, we developed a predictive index based on Veterans Affairs data70 and have since shown that the risk of covid-19 mortality associated with age, sex, and comorbid disease diagnoses that we observed in Veterans Affairs data was consistent across other academic and national healthcare samples in the US 71. Our key finding in the current analysis has also been shown in smaller, non-veteran healthcare systems1314; thus, effects reported in this study are probably generalizable to the wider US population.…”
Section: Discussionmentioning
confidence: 99%
“…The VACO Index, a 30-day all-cause mortality prediction model developed in VA nationwide data, utilizes demographic and pre-existing condition data available in EHR or medical administrative data [5]. The Index includes age, sex, multimorbidity quantified with the Charlson Comorbidity Index derived from International Classification of Diseases, 10th edition (ICD-10) diagnosis codes [9, 10] (S1.…”
Section: Methodsmentioning
confidence: 99%
“…The Veterans Health Administration COVID-19 (VACO) Index for short term mortality is based on age, sex, and comorbid diagnoses [5]. It was developed based on 3,681 SARS-CoV-2 positive patient records from the Veterans Healthcare Administration (VA) national electronic health record (EHR) and prospectively validated in 9,642 veterans split into two temporally distinct samples.…”
Section: Introductionmentioning
confidence: 99%
“…Hypoxaemia was defined as having oxygen saturation below 93% or the need of oxygen support to maintain saturation above 93% [2,7]. We selected a priori set of potential predictors according the availability of data in the HIS and whether the variables had shown to influence the outcome of COVID-19 in previous studies [8][9][10][11][12][13].…”
Section: Outcome and Independent Predictorsmentioning
confidence: 99%